Human eosinophil chemotaxis and selective in vivo recruitment by sphingosine 1-phosphate - Roviezzo, Fiorentina (National Academy of Sciences, 2004)
Sphingosine 1-phosphate (S1P) is a sphingolipid mediator that is involved in diverse biological functions. Local administration of S1P causes inflammation coupled to a large eosinophil (EO) recruitment in the rat-paw tissue. The inflammatory response is accompanied by an increase in S1P receptors, namely S1P(1), S1P(2), S1P(3), and by an enhanced expression of CCR3, which is the main chemokine receptor known to be involved in EO function. Human EOs constitutively express S1P(1) and, at a lower extent, S1P(2), S1P(3) receptors. S1P in vitro causes cultured human EO migration and an increase in S1P receptor mRNA copies and strongly up-regulates CCR3 and RANTES (regulated on activation, normal T cell-expressed and secreted) message levels; in particular CCR3 is up-regulated 18,000-fold by S1P. A blocking anti-CCR3 Ab inhibits S1P-induced chemotaxis, implying that S1P acts as specific recruiting signal for EOs not only through its own receptors but also through CCR3. These results show that S1P is involved in EO chemotaxis and contribute to shed light on the complex mechanisms underlying EO recruitment in several diseases such as asthma and some malignancies.